(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Children’s Hope hospital is a healthcare institution providing patient treatment with specialized state and medical equipment that helps children with unconditional diseases. Children’s Hope Hospital offered its service exclusively to those children from birth up to 12 years old. A quantitative research method was used to conduct the study. Purposive sampling was used to select respondents in assessing the level of acceptability of Children’s Hope Hospital by using a survey questionnaire. The researchers surveyed to determine whether the proposed project is acceptable in terms of construction materials, procedural methodology, and presentation. The results of the study in terms of construction materials, procedural methodology, and presentation were acceptable, as assessed by Civil Engineering students and Architecture students. This result indicated no significant difference between the assessment of the two groups of respondents in terms of the cited variables. Civil Engineering students acquired an overall mean of 2.79, with a variance of 0.286, a t-computed mean of 3.68, and a degree of freedom of 18 with a value of 1.734. The t-computed value was larger than the t-critical one. Therefore, the assessment of the Architecture students is accepted. Meanwhile, the acquired overall mean of Architecture students was 3.11 with a variance of 0.004, and the t-computed value was larger than the t-critical one. Therefore, the assessment of the Civil Engineering students is accepted. The Children’s Hope Hospital has a standard scale of 1 m:2 cm. It is also designed to accumulate each floor in one place. It is 9 cm high from the ground to the roof and 20 cm in width, which is the standard. The building has 3 floors, which is shown in the outer or exterior design of the model. At the construction of the Children’s Hope Hospital model, the platform used Styrofoam as a molder. Next is the construction of the structure. At first, we used glue to paste the cardboards as walls into the Styrofoam, but we failed. Thus, we tried to use wood glue, and it worked. Then, after pasting all cardboards, we used orange acrylic paint to the roof as an exterior design. Lastly, we used yellow and black acrylic paints to polish and add colors to the whole design for the structure and design the exterior ground floor by using green sponges as grass and plants.